The practice of ambidextrous management by means of public health business advancement by an old-established liquor company: Discontinuity & radical innovation practiced by Meiri Shurui Co., Ltd. - Hirofumi OTA (AAOS Transactions)
How did a company exposed to a harsh business environment embody ambidextrous management and result in fundamental restructuring of management in trouble? This article aimed at unveiling from interviews with executives qualitatively the ambidextrous mechanism to practice radical innovation based on a case of the public health business advancement by an old-established liquor company with the coronavirus pandemic in addition to the strict liquor market environments. It is implied that second son of the founding family who worked for an external company until coronavirus pandemic accelerated corporate transformation and lead radical innovation of the family firm, while family firms are not positive about radical innovation.